2014
DOI: 10.1016/j.ihj.2014.10.415
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic importance of admission platelet volume indices in patients with acute chest pain suggesting acute coronary syndrome

Abstract: An elevated admission MPV, PDW, and P-LCR may be of benefit to detect chest pain resulting in MI from that of non-cardiac one, and also for risk stratification of patients who suffered from an acute chest discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
1
11
1
2
Order By: Relevance
“…The reason for the reduced MPV in acute appendicitis is unclear, but the reduced MPV could be due to the consumption or sequestration of the large activated platelets in intestinal vasculature 22 . In addition to sepsis and various infections, MPV also has a positive correlation with many different diseases such as diabetes, myocardial infarction and young children with infections and varying degrees of the cut-off value (8.0–10.35 fL), sensitivity (53–98%) and specificity (35–87%) 23 24 25 26 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the reduced MPV in acute appendicitis is unclear, but the reduced MPV could be due to the consumption or sequestration of the large activated platelets in intestinal vasculature 22 . In addition to sepsis and various infections, MPV also has a positive correlation with many different diseases such as diabetes, myocardial infarction and young children with infections and varying degrees of the cut-off value (8.0–10.35 fL), sensitivity (53–98%) and specificity (35–87%) 23 24 25 26 27 .…”
Section: Discussionmentioning
confidence: 99%
“…This combined marker has been investigated recently in multiple studies as a marker of more severe atherosclerosis and outcomes after elective and emergency PCI. A high PLT/LYM was associated with more complex CAD in patients with acute coronary syndromes [19,20], and with complete occlusion of the infarct related artery in patients with STEMI [21]. In a recent study a higher incidence of CTO was found in patients with a PLT/LYM greater than 116 [19].…”
Section: Platelet-to-lymphocyte Ratio As An Independent Predictor Of mentioning
confidence: 90%
“…Compared to healthy controls, P-LCR is higher in patients with acute myocardial infarction and unstable angina [12,13]. None of the published studies correlating platelet indices with CAD and especially with STEMI present data on the associations between CTO and P-LCR.…”
Section: Platelet Indices and Ctomentioning
confidence: 99%
See 1 more Smart Citation
“…It could also be used as a marker of platelet reactivity as well as an index for short term mortality of coronary artery disease and the risk of thrombolysis failure [ 11 ]. Further, PDW is considered as a more specific parameter for the activation than MPV, as it does not increase during simple platelet swelling [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ].…”
Section: Introductionmentioning
confidence: 99%